2020 Physics Education Research Conference Proceedings 2020
DOI: 10.1119/perc.2020.pr.pearson_iii
|View full text |Cite
|
Sign up to set email alerts
|

Faculty perception insights obtained from faculty interviews during the development of the Perceptions of Teaching as a Profession in Higher Education (PTaP.HE) instrument

Abstract: Results from the Perceptions of Teaching as a Profession (PTaP) instrument-which measures views students have of the grade 7-12 teaching career-prompted the development of a parallel instrument to measure the perceptions of the grade 7-12 teaching profession in the eyes of those advising and influencing student opinions of the profession: the faculty. Thirty faculty interviews were conducted across four different institutions of higher education as part of the development of the Perceptions of Teaching as a Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Analyzing PTaP.HE survey responses based on the factors that emerged from the RBFA provide further insight into faculty thinking about the teaching career. In previous work, interviews identified that faculty believe they are supportive of students who want to become teachers [7]. This was validated by these data that show Supportive Department Messaging, Career Options, Teaching is a STEM Profession, and Teaching is an Attractive STEM Career, all have high (over 70%) average percent favorable scores.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…Analyzing PTaP.HE survey responses based on the factors that emerged from the RBFA provide further insight into faculty thinking about the teaching career. In previous work, interviews identified that faculty believe they are supportive of students who want to become teachers [7]. This was validated by these data that show Supportive Department Messaging, Career Options, Teaching is a STEM Profession, and Teaching is an Attractive STEM Career, all have high (over 70%) average percent favorable scores.…”
Section: Discussionmentioning
confidence: 64%
“…Perception surveys and concept inventories (such as the PTaP [9] and CLASS [8]) follow a general but consistent four-phase development and validation structure as summarized by Adams and Wieman [10] and to which the PTaP.HE development generally adheres. Here we will focus on the validation efforts in Phase Four as Phases One through Three were described in previous work [7].…”
Section: B Development and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…1 to 5) [13][14][15][16][17][18][19][20][21][22][23][24]; binning responses into a binary categorization (e.x. agree or disagree) [25][26][27][28][29][30][31][32][33][34]; or binning into a simple point scale and then averaging (e.x. binned point values of -1,0,1 and then averaging) [35][36][37][38].…”
Section: Background and Motivationmentioning
confidence: 99%